Sobre enraizamento de estacas de cacaueiro - Rochelle, Luiz Antonio; Igue, Toshio; Cunha, João Ferreira da (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1965)
We present here the results obtained by application of two differens hormones on cuttings of Theobroma leiocarpa, Bern. We are using naphtalene acetic acid and indole-butiric acid. The treatments consisted in inversion of the lower end of the cuttings in solution of liguid hormoni for 24 hours. The indole-butiric acid, in concentration 100 mg in 1000 ccs of water, gave the best results.